Identificación de insectos polinizadores en la ribera del rio Cutuchi sector puente Benjamín Terán hasta la calle Félix Valencia de la ciudad de Latacunga provincia de Cotopaxi-2023. - Gallegos Flores, Pablo Miguel (2023)
The present research work was carried out in the urban area of the city of Latacunga at latitude -0.926096 and longitude -78.624158, at 2,685 m above sea level. The objective of the study was to identify different pollinating insects on the banks of the Cutuchi River, urban area, from the Benjamín Teran bridge sector to Feliz Valencia Street in the city of Latacunga, as well as to establish diversity indicators. Active collection was carried out using insect nets and passive collection using coloured sticky traps and baited traps. The samples were preserved in 70% alcohol, then mounted and photographed and uploaded to the iNaturalist extension, in order to identify the individuals collected. At the same time, 813 individuals were collected in the chromatic sticky traps, 2 individuals were obtained with the Harris trap and 337 individuals with the entomological net. After the capture, we proceeded to the identification of individuals, in this case we only considered the pollinating individuals, giving us the Apidae family in a total of 27.27% and the other families in a total of 9.09%, indicating which was the dominant family of the individuals obtained in the Cutuchi river bank.